Clinical Supervision Training to Improve Teacher Professionalism Competence at Mts Darul Falah Tulungagung: Pelatihan Supervisi Klinis dalam Meningkatkan Kompetensi Profesionalisme Guru di MTS Darul Falah Tulungagung - Masrokan Mutohar, Prim; Sukur, Mukhamad; Rikza Alkhubra Abdul Jabbar, Moch; Dwi Anissa, Desi (Universitas Haji Sumatera Utara, 2025)
Teacher professionalism is the spearhead in improving the quality of education in schools or madrasas, because teachers directly interact with students in all learning activities. Teacher professionalism must be continuously improved by implementing teacher competency development by the principal as supervisor. This development can be implemented with a clinical supervision approach that prioritizes solving teacher teaching problems authentically. Clinical supervision is an option that can be used by principals to continuously develop teachers' competencies. The implementation of clinical supervision was carried out at Islamic Middle School Darul Falah Tulungagung through Participatory Action Research (PAR) activities involving the madrasah principal and teachers in every stage of the activity, from training, implementation of clinical supervision, to evaluation. The results of the activity showed that the madrasah principal was able to understand the concept of clinical supervision and apply it in implementing teacher development to become professional. Clinical supervision was carried out through pre-conference, conference, and post-conference stages that involved supervisors and teachers in diagnosing difficulties experienced by teachers and efforts to improve them continuously. The implementation of clinical supervision has been proven to improve teachers' teaching skills, which can lead to improved student achievement in Islamic schools. Evaluation of the activity indicates increased self-confidence, openness to feedback, and a collaborative spirit among teachers. Thus, this activity makes a significant contribution to improving the quality of learning and teacher professionalism in Islamic educational institutions.